Geopolitical Inhomogeneities in the Registered Voters’ Distribution and Their Influence in the Voters’ Participation Ratio Distribution: The Mexican Case - Hernández-Saldaña, H. (Frontiers in Applied Mathematics and Statistics, 2021)
Stylized facts appear in electoral processes, from Brazil to India. Here, we update a statistics carried on in Mexican elections but considering the inhomogeneities in electoral districts through the nominal list , NL,(the list of valid electors in a given decision process). The usual assumption of a gaussian distribution is contrasted with the data from the last three presidential elections. We find that taken in to account the inhomogeneities we find a better fitting theoretical probability distribution. Such a function is a skewed gaussian, that is close to the experimental one, at least for the bulk part. The results is regardless from municipality, political district or urban vs non-urban distinction. We argue that the observed asymmetry is just a consequence of the correlation in the variables and no only to the constrain in the sample. Hence, the distribution of the voters participation ratio is not a gaussian or a truncated gaussian.